Effects of superplasticizers on workability and concrete strength - Ahmad Hanis Bin Jamil Rashid (School of Environmental Engineering, University Malaysia Perlis, 2014)
This research investigates the effects of superplasticizers on workability and strength in concrete mixture. Sulphonated naphthalene formaldehyde (SNF), one of four classes of superplasticizers has been chose in this research. SNF has been chose based on its low cost production and commonly used around the world. Hence, it is easier to gain rather than other classes.